2022
DOI: 10.1021/acsnano.2c02529
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Self-Assembly of Interfaces of 2D Metal–Organic Frameworks for Electroanalytical Detection of Neurotransmitters

Abstract: This paper identifies the electrochemical properties of individual facets of anisotropic layered conductive metal–organic frameworks (MOFs) based on M 3 (2,3,6,7,10,11-hexahydroxytriphenylene) 2 (M 3 (HHTP) 2 ) (M = Co, Ni). The electroanalytical advantages of each facet are then applied toward the electrochemical detection of neurochemicals. By employing epitaxially controlled deposition of M 3 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…In the X-ray powder diffraction (XRD) experiment, 2θ of the diffraction peaks was located at ≈4.8°, ≈9.6°, ≈12.7°, and ≈28°, respectively, corresponding to the (100), ( 200), (210), and (001) planes, 9,11,40,45,46 as shown in Figures 2A and S2. The hk 0 reflection in XRD experiments, 40 especially in the region of about 2θ ≈ 26°, was relatively sharp.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the X-ray powder diffraction (XRD) experiment, 2θ of the diffraction peaks was located at ≈4.8°, ≈9.6°, ≈12.7°, and ≈28°, respectively, corresponding to the (100), ( 200), (210), and (001) planes, 9,11,40,45,46 as shown in Figures 2A and S2. The hk 0 reflection in XRD experiments, 40 especially in the region of about 2θ ≈ 26°, was relatively sharp.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the X-ray powder diffraction (XRD) experiment, 2θ of the diffraction peaks was located at ≈4.8°, ≈9.6°, ≈12.7°, and ≈28°, respectively, corresponding to the (100), ( 200), (210), and (001) planes, 9,11,40,45,46 as shown in Figures 2A and S2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Because of the high surface area of MOFs, several previous studies have demonstrated the direct use of water-stable MOFs as the active materials for electrochemical DA detection. For example, Mirica et al demonstrated the use of two-dimensional conductive MOFs for electrochemical DA detection . Wu and coworkers reported one of the first attempts at the use of the highly porous and water-stable Zr-MOFs in electrochemical DA sensors .…”
Section: Introductionmentioning
confidence: 99%
“…14 Electrochemical sensing parameters have improved with the evolution from naturally occurring graphitic materials to synthetic materials such as conducting polymers, MXenes, and metal alloy nanoparticles (NPs). [14][15][16][17] Research on conducting polymers (CPs), particularly PEDOT, has seen tremendous strides owing to their intrinsic advantages of high electrical conductivity, optical transparency, low redox potential, high environmental stability, and biocompatibility. [18][19][20] Chemical polymerization using oxidizing agents or electro-polymerization, using a potential applied across a monomer solution, are the two frequently exploited methods for the effectual nanostructure tuning of CPs.…”
Section: Introductionmentioning
confidence: 99%